An interdisciplinary approach to enhance children’s listening, learning, and wellbeing in the classroom: The Listen to Learn for Life (L3) Assessment Framework - Mealings, Kiri; Miles, Kelly; Parrila, Rauno; Holt, Rebecca; Cox, Felicity; Dillon, Harvey; Sharma, Mridula; Demuth, Katherine; Leigh, Greg; McMahon, Catherine; McArthur, Genevieve; Buchholz, Joerg M. (Frontiers in Education, 2023)
Introduction: Listening is the gateway to children learning in the mainstream classroom. However, modern classrooms are noisy and dynamic environments making listening challenging. It is therefore critical for speech and hearing researchers from speech and hearing, education, and health sciences to co-design and collaborate researchers to realistically assess how children listen to learn in the classroom and to understand how listening can be improved to enhance children's learning and wellbeingan understanding which is currently lacking. Such highly interdisciplinary thinking demands a holistic classroom listening framework that can integrate a range of varied assessments and outcomes.Method: An extensive review of literature into classroom listening was conducted but failed to identify a suitable framework. In this hypothesis and theory article we present a new framework that we have developedthe Listen to Learn for Life (L 3 ) Assessment Framework.Results: The L 3 Assessment Framework holistically incorporates frameworks from health, speech and hearing sciences, and education sectors. The framework accommodates a broad range of different factors that may affect listening, allowing for researchers to choose specific factors dependent on the context of use.Discussion: Selected examples of applying the framework are provided demonstrating how to assess children's performance during different classroom activities as well as the effectiveness of a chosen intervention. For example, the framework can be used to assess the effectiveness of a wireless remote microphone intervention during group work activities for a child with autism.Conclusions: The L 3 Assessment Framework provides a theoretical basis for the future development of research and practice as applied to listening in a classroom setting.